Falling Rates of Hospital Admissions for Alcoholic Liver Disease in Northeast Italy: A Retrospective Study on a Large Database. (30th September 2019) - Caroli, Diego; Rosa-Rizzotto, Erik; Pilerci, Claudio; Lobello, Salvatore; De Lazzari, Franca; Saia, Mario
Abstract: Aim: To describe recent trends in hospital admission rates for alcoholic liver disease (ALD) in the Veneto region of Italy. Methods: This retrospective cohort study is based on anonymous hospital discharge records (HDRs) for 2000–2017 from all public and accredited private hospitals operating within the context of the Regional (Veneto) Health Services that are conserved in National/Regional database. It examined the HDR's of all the hospitalizations of the residents of the Veneto region that were registered under an ALD diagnosis. These were classified under three subheadings: acute alcoholic hepatitis Alcoholic liver cirrhosis and 'other ALD'. Results: During 2000–2017, 30, 089 hospital admissions (out of a total regional population of 4, 900, 000) were registered for ALD. Hospitalization stratified by age showed that the percentage attributable to acute alcoholic hepatitis is higher in younger age groups: 42% in 15–24-year-old (odds ratios (ORs): 14.74; CI95%: 7–30.86; P < 0.000) and 15% in the 25–44-year-old (OR: 3.51; CI95%: 3.12–3.94; P < 0.000). A longitudinal analysis of hospitalization patterns showed a 7% increase in average age in both sexes (from 58.8 ± 9.2 to 62.4 ± 9.7) and a substantial decrease (63.5%) in standardized hospitalization rates (HRs, χ 2 trend: 4099.827; P < 0.000) and a smaller decrease (47%) in standardized mortality rates ( χ 2 trend: 89.563; P < 0.000). Conclusions: The fall in the overall ALD-related HR in the Veneto region can be explained by a decrease in population alcohol consumption. Increase in the HRs for acute alcoholic hepatitis in the age group 15–44 suggests an ongoing need for strategies to prevent alcohol abuse by young people. Abstract : In the observation period, there is a constant decline in hospitalizations for alcoholic liver disease probably due to falling alcohol consumption; however, increase in the rates in the 25–44 age group until 2015 suggests the need to reduce alcohol abuse by young people (males in particular).